Are we forgetting to carry out serum protein electrophoresis as part of diagnosis workup? - Mariana Barros Marcondes; Cíntia Mitsue Pereira Susuki; Newton Key Hokama; Paula de Oliveira Montandon Hokama; Felipe Aguera Oliver; Paulo Sergio Chaib; Xingshun Qi; Fernando Gomes Romeiro (BMC Gastroenterology, 2022)
Abstract Background Common variable immunodeficiency (CVID) is a rare disease that affects children and adults and is often difficult to diagnose. Despite being one of the most frequent causes of immunodeficiency, involving gastrointestinal (GI), respiratory, and hematological systems, the disease onset can have heterogeneous and intermittent symptoms, frequently leading to diagnostic delay. GI symptoms are common and can include diarrhea, but the asymptomatic periods lead to overlooking the recurrent pattern. The same can occur with respiratory infections, thus delaying CVID suspicion. The starting point for CVID diagnosis is the decreased gamma globulin levels in serum protein electrophoresis (SPE), also observed through direct immunoglobulin’s dosage. Case presentation The patient is a 38 years-old man who had intermittent diarrhea and recurrent airway infections for 19 years, but the CVID diagnosis was achieved only after SPE was carried out. At that time, he was already malnourished, and developed other complications related to CVID in a short period. Conclusions SPE is readily available and inexpensive, but is not part of the laboratory approach in diarrhea. According to the case presented herein, it can be useful for patients with recurrent infections or other clues of the disease.